Long‐term outcome and neuroradiologic changes after multiple hippocampal transection combined with multiple subpial transection or lesionectomy for temporal lobe epilepsy. (15th April 2016) - Usami, Kenichi; Kubota, Mayumi; Kawai, Kensuke; Kunii, Naoto; Matsuo, Takeshi; Ibayashi, Kenji; Takahashi, Miwako; Kamada, Kyousuke; Momose, Toshimitsu; Aoki, Shigeki; Saito, Nobuhito
Summary: Objective: Multiple hippocampal transection (MHT) is a surgical procedure developed to avoid postoperative memory decline. Its efficacy has been documented in only a few small series with relatively short observation periods. We prospectively evaluated the long‐term seizure and cognitive outcomes of MHT combined with multiple subpial transection or lesionectomy (MHT + MST/L). Moreover, we quantitatively evaluated the structural and metabolic neuroradiologic changes after the procedure to elucidate the anatomofunctional correlates of memory preservation. Methods: Twenty‐four patients underwent MHT + MST/L for treatment of drug‐resistant mesial temporal lobe epilepsy (mTLE) and were followed for more than 5 years. Indications for the procedure were the following: (1) verbally dominant‐sided surgery in patients with a radiologically normal hippocampus or normal/near normal memory, and (2) surgery for patients with concomitant epileptic activity on the contralateral side, that is, when the surgery was considered a high risk for severe postoperative memory decline. Seizure outcome was evaluated using Engel's classification 1, 2, and 3 years after surgery, and at the last visit (LV). Three subgroups were evaluated as well: magnetic resonance imaging (MRI) negative (MN), hippocampal sclerosis (HS), and normal hippocampus with extrahippocampal lesion (NHEL). The long‐term cognitive outcome was followed through to LV in patients who underwent verbally dominant‐sided surgery. Hippocampal volume (HV), diffusion tensor parameters (DTP), and glucose utilization (GU) were determined from MRI and fluorodeoxyglucose–positron emission tomography (FDG‐PET) studies performed before and >6 months after surgery. Results: Whereas the rate of Engel class I as a whole was 71% at 1 year and 67% at LV, the rates in the MN, HS, and NHEL groups were 60%, 67%, and 100% at 1 year, respectively, and 70%, 56%, and 80% at LV, respectively. Memory indices after verbally dominant‐sided surgery transiently declined at 1 month but recovered to and remained at the preoperative level through LV. The HV, DTP of the fornix, and GU of the temporal lobe on the treated side showed pathologic changes even when the transiently declined memory indices had recovered to the preoperative level. Significance: The long‐term outcome for complex partial seizures after MHT + MST/L was comparable to that seen after anterior temporal lobectomy. The long‐term cognitive outcome was favorable, even for patients with a high risk of severe postoperative memory decline. MHT + MST/L may be a treatment option for mTLE in which resective surgery carries a risk of postoperative memory decline, particularly in patients without MRI lesion. A discrepancy between the preserved memory and the pathologic neuroradiologic changes indicates the necessity for further studies including functional MRI.